2022
DOI: 10.3389/fimmu.2022.1020003
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapeutic progress and application of bispecific antibody in cancer

Abstract: Bispecific antibodies (bsAbs) are artificial antibodies with two distinct antigen-binding sites that can bind to different antigens or different epitopes on the same antigen. Based on a variety of technology platforms currently developed, bsAbs can exhibit different formats and mechanisms of action. The upgrading of antibody technology has promoted the development of bsAbs, which has been effectively used in the treatment of tumors. So far, 7 bsAbs have been approved for marketing in the world, and more than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 133 publications
0
13
0
Order By: Relevance
“…5 Bispecific antibodies can simultaneously bind two different antigens or two nonoverlapping epitopes, providing therapeutic effects unattainable by mAb or cocktails of mAbs, as well as safety and efficiency advantages. 21,22 At present, bispecific antibodies are widely used in the field of tumor therapy. In viral immunotherapy, the applications of bi-or multispecific antibodies are emerging to overcome viral genetic diversity and prevent viral escape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Bispecific antibodies can simultaneously bind two different antigens or two nonoverlapping epitopes, providing therapeutic effects unattainable by mAb or cocktails of mAbs, as well as safety and efficiency advantages. 21,22 At present, bispecific antibodies are widely used in the field of tumor therapy. In viral immunotherapy, the applications of bi-or multispecific antibodies are emerging to overcome viral genetic diversity and prevent viral escape.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main difficulty in producing asymmetric IgG‐like bispecific antibodies lies in solving the mismatch problem of antibody heavy chain and light chain separately. So far, many technical platforms have been developed to overcome this problem, including Knobs‐into‐Holes (KIH), Crossmab, Triomab quadroma, DuoBody, and so on 22 . To prevent heavy chain mismatch, we adopted classical KIH technology to promote the formation of heterodimers.…”
Section: Introductionmentioning
confidence: 99%
“…A bispecific antibody (BsAb) is a class of structurally bivalent antibody molecules with two different specific antigen-binding sites. Studies have shown that BsAb can be used to enhance the antitumor efficacy and play an important role in immunotherapy. , Because its structure is suitable for multicomponent residue analysis, it has been paid more and more attention, but the preparation method is not mature enough, and its application is few. In this study, bispecific monoclonal antibodies (BsMAbs) were prepared by the hybridization-hybridoma technique, , providing a reference for the simultaneous identification of two small molecules of different classes.…”
Section: Introductionmentioning
confidence: 99%
“…Bispecific antibodies (bsAbs) are attractive as they are capable of recruiting immune cells to attack tumors or increasing binding specificity. Owing to recent advances in antibody conjugation methodologies, more than 200 types of bsAbs have been made for clinical and preclinical trials . However, many of these synthetic strategies are incapable of incorporating the Fc domain that could confer bsAbs with higher stability, better solubility, longer half-life, and enhancement of tumor killing capacity due to Fc-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) and complement dependent cytotoxicity (CDC) effects .…”
mentioning
confidence: 99%
“…Owing to recent advances in antibody conjugation methodologies, more than 200 types of bsAbs have been made for clinical and preclinical trials. 2 However, many of these synthetic strategies are incapable of incorporating the Fc domain that could confer bsAbs with higher stability, better solubility, longer half-life, 3 and enhancement of tumor killing capacity due to Fc-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) and complement dependent cytotoxicity (CDC) effects. 4 Existing methods for producing Fc-containing IgG-like bsAbs are almost exclusively protein bioengineering, including quadroma cell line technology, 5 "knobs-into-holes", 6 Cross-Mab, 7 etc.…”
mentioning
confidence: 99%